The Impact of the COVID-19 Pandemic on the Profitability of the Banking Sector in Poland - Ostrowska, Aleksandra (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2021)
Objective: To assess the impact of the COVID-19 pandemic on the profitability of the banking sector in Poland. Research Design & Methods: The methodologies included critical literature analysis and statistical data analysis. Findings: The profitability ratios of the banking sector in Poland deteriorated during the COVID-19 pandemic. Implications/Recommendations: The economic slowdown due to government restrictions introduced in response to the COVID-19 pandemic took a toll on the banking sector in Poland, which has been weakening for several years. However, the factor that determined the decrease in the financial results and, consequently, the profitability of the banking sector in Poland to the greatest extent was the increase in provisions and write-offs for the legal risk of FX housing loans. This situation calls for corrective measures. Contribution: An assessment of the effects of a COVID-19 pandemic on the banking sector in Poland.